2019
DOI: 10.1021/acs.jafc.9b03235
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Key Binding Sites of Sex Pheromone-Binding Proteins from the Meadow Moth, Loxostege sticticalis

Abstract: The meadow moth, Loxostege sticticalis, is a typical agricultural pest that uses sex pheromones to mediate mating behavior; however, the mechanism underlying the selectivity of its pheromone-binding proteins (PBPs) remains unknown. In this study, LstiPBP1 and LstiPBP3 were cloned, expressed, and purified, and the fluorescence binding assay showed that LstiPBP1 binds to the major sex pheromone component, E-11-tetradecenol (E11-14:OH), with high affinity; moreover, E11-14:OH could evoke a significant antennal el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…Our results revealed that M39A, V68A, W106A, Q107A, and Y114A mutant proteins lost their ability to bind the ligands, suggesting that these residues may be involved in the binding affinity of AlepOBP6 to distinct ligands (key residues of Z 7‐12:Ac: W106 and Y114; Z 9‐14:Ac: V68, W106, and Y114; n ‐nonane and 1‐octen‐3‐ol: M39; (−)‐limonene, n‐nonane, benzaldehyde, decanal, 1‐octen‐3‐ol: Q107; Z 9‐14:Ac, α‐pinene, myrcene, 2‐hexanone, 2‐heptanone, 6‐methyl‐5‐hepten‐2‐one: V68 and Y114). Some studies have confirmed that the mutation of putatively crucial residues to alanine leads to a loss or decrease in the binding ability of OBPs to sex pheromones and host volatiles in other insects, 52,60,61,63–65 and this corresponds with our results. However, we also found no significant difference in the binding affinity of three ligands, (−)‐limonene, benzaldehyde and decanal, between M39A mutant and wild‐type AlepOBP6, which may be due to the bioinformatics prediction not being able to fully simulate the complex internal environment of insects.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results revealed that M39A, V68A, W106A, Q107A, and Y114A mutant proteins lost their ability to bind the ligands, suggesting that these residues may be involved in the binding affinity of AlepOBP6 to distinct ligands (key residues of Z 7‐12:Ac: W106 and Y114; Z 9‐14:Ac: V68, W106, and Y114; n ‐nonane and 1‐octen‐3‐ol: M39; (−)‐limonene, n‐nonane, benzaldehyde, decanal, 1‐octen‐3‐ol: Q107; Z 9‐14:Ac, α‐pinene, myrcene, 2‐hexanone, 2‐heptanone, 6‐methyl‐5‐hepten‐2‐one: V68 and Y114). Some studies have confirmed that the mutation of putatively crucial residues to alanine leads to a loss or decrease in the binding ability of OBPs to sex pheromones and host volatiles in other insects, 52,60,61,63–65 and this corresponds with our results. However, we also found no significant difference in the binding affinity of three ligands, (−)‐limonene, benzaldehyde and decanal, between M39A mutant and wild‐type AlepOBP6, which may be due to the bioinformatics prediction not being able to fully simulate the complex internal environment of insects.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have shown that insect OBPs usually bind distinct ligands with nonpolar and polar amino acid residues in a hydrophobic cavity 37,43,52,60–62 . Based on analysis of the binding models of AlepOBP6 to all 12 ligands, we also found that there were key nonpolar and polar residues involved in AlepOBP6 binding, suggesting that its ligand binding mechanism is consistent with that of insect OBPs 40–44 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Oliveira et al [ 101 ] has reported the use of RNAi technique to identify the PBP RproOBP27, involved in sex pheromone detection of Rhodnius prolixus. Identification and molecular characterization of PBPs from multiple insect species, such as Cydia pomonella [ 100 ], Chilo suppressalis [ 102 ], Loxostege sticticalis [ 103 ], and Conogethes pinicolalis [ 104 ] have been reported in recent years. PBP1 from S. exigua [ 105 ] and Cyrtotrachelus buqueti [ 106 ] can also bind to plant volatile compounds, such as benzaldehyde, linalool, indole, and other carboxylic acids, in addition to pheromone molecules.…”
Section: Mechanisms Of Insect Sex Pheromone Perceptionmentioning
confidence: 99%